PENERAPAN ELEMEN INTEGRATED REPORTING DALAM LAPORAN TAHUNAN TERHADAP NILAI PERUSAHAAN TAHUN 2017 - 2019 (Studi Kasus Perusahaan yang Terdaftar Di Indeks IDX30) - Sri Handayani; Lydia Maheswari; Dheny Biantara (Universitas Agung Podomoro, 2021)
This research aims to see how the Integrated Reporting elements have been implemented in the annual report from companies listed in the Indonesia Stock Exchange IDX30 index. It is also showing the correlation between the Integrated Reporting content element implementation with the company’s value based on the share closing price per year, price to book value and price earning ratio. The sample used in this research is the 2017 to 2019 company’s annual report that has been published. This is qualitative research using the descriptive explanatory method. This research captures how the implementation of the Integrated Reporting content element that appeared on the annual report affects the company’s value based on closing share price, price to book value and price earning ratio. The result of this research is the implementation of integrated reporting elements has no significant impact on the share closing price per year and has a quite significant impact on price to book value and price earning ratio.